Planos de luz do ambiente na preparação para reprodução de fêmeas de Tilápia Nilótica (Oreochormis niloticus) - Grossi, Aline Junqueira (2019)
Aquaculture is the food production activity that has expanded worldwide the most in recent years. Meanwhile, nile tilapia is the second most produced fish species in the world. In general, tilapia species have favorable reproduction characteristics but one issue for producers is that the tilapia is asynchronous, which means it cannot form many families in a short period of time. Thus, the present study aimed to evaluate how different colors of light and days of exposure influenced the preparation for the reproduction of nile tilapia (UFLA lineage females). A total of 192 females were randomly distributed in 16 water tanks of 500 liters with 12 females each, and submitted to four types of lights (blue, green, red, and white) and four exposure times (14, 21, 28, and 35 days). At the end of each period, blood was collected from all animals for glucose analysis. Five females from each box were euthanized at the end of each exposure period for gonad and liver collection, and the other females were extruded to evaluate the oocyte maturation stage. The animals were identified and their morphometric measurements and weights were measured at the beginning and end of each period of the experiment. For the differences between the treatments (colors and exposure times), an analysis of variance analysis (ANOVA) was performed for the morphometric and reproductive variables submitted to the Ducan test, to show the differences between the averages using final weight (PF) and initial weight (PI). An analysis of multiple linear regression was performed to relate the differences between the response variables and the dependent variable. We observed that the blue and white lights led to higher fish weigh gain during the whole experiment, and that the green color led to higher liver and gonadal weigh. The longer the fish were exposed (35 days), the better was the overall performance. According to the results, the color of the light, exposure time, and the relationship between color and exposure time are important factors for the nile tilapia reproductive performance, affecting the growth and development of the fish.